Menyelaraskan Keyakinan dan Pembelajaran; Menggali Dinamika Internalisasi Islam dalam Dikotomi Pendidikan - Purnawanto, Ahmad Teguh; Anif, Sofyan; Prayitno, Harun Joko; Muhibbin, Ahmad (QUALITY, 2024)
Aligning Beliefs and Learning; Exploring the Dynamics of Islamic Internalisation in Educational Dichotomy. Islamic education offers mercy for all nature that is able to guide the lives of all nature. Islamic education faces challenges in the global era that confronts the competence of modern life. Changes in the pattern and form of Islamic education must be able to answer the needs of the times. Islamic education must strive to never stop the process of building and educating the nation's children across generations. This research aims to investigate the relationship between belief and learning in the context of the dynamics of Islamic internalisation in the dichotomy of education. Education is often regarded as a platform for transmitting religious values, including Islam, to the younger generation. The research method involves a qualitative study with a literature review phenomenological approach to understand the relationship between the dichotomy of science and Islamic education in Indonesian human character education. Thematic analysis was conducted to identify major themes and patterns in the literature. The results provide an in-depth understanding of how beliefs are influenced by learning experiences, as well as the extent to which formal and informal experiences play a role in the internalisation of Islamic values. Islamic education should be implemented through an interdisciplinary educational approach that integrates Islamic concepts and values with other disciplines. The practical implications of this research can be used to develop more effective learning methods in responding to learners' spiritual and moral needs, while considering the dynamics of Islamic internalisation in the two dimensions of education.Pendidikan Islam menawarkan rahmat bagi seluruh alam yang mampu menjadi penuntun kehidupan seluruh alam. Pendidikan Islam menghadapi tantangan dalam era global yang menghadapkan pada kompetensi kehidupan modern. Perubahan pola dan bentuk pendidikan Islam harus mampu menjawab kebutuhan jaman. Pendidikan Islam harus diusahakan untuk tidak pernah berhenti berproses dalam membangun dan mencerdaskan anak bangsa lintas generasi. Penelitian ini bertujuan untuk menyelidiki hubungan antara keyakinan dan pembelajaran dalam konteks dinamika internalisasi Islam dalam dikotomi pendidikan. Pendidikan seringkali dianggap sebagai wadah untuk mentransmisikan nilai-nilai agama, termasuk Islam, kepada generasi muda. Metode penelitian ini melibatkan studi kualitatif dengan pendekatan fenomenologi literature review untuk memahami hubungan antara dikotomi ilmu dan pendidikan Islam dalam pendidikan karakter manusia Indonesia. Analisis tematik dilakukan untuk mengidentifikasi tema utama dan pola dalam literatur. Hasil penelitian memberikan pemahaman mendalam tentang bagaimana keyakinan dipengaruhi oleh pengalaman pembelajaran, serta sejauh mana pengalaman formal dan informal berperan dalam internalisasi nilai-nilai Islam. Pendidikan Islam sebaiknya dilaksanakan melalui pendekatan pendidikan interdisipliner yakni pendekatan pendidikan yang mengintegrasikan konsep dan nilai-nilai agama Islam dengan disiplin ilmu lainnya. Implikasi praktis dari penelitian ini dapat digunakan untuk mengembangkan metode pembelajaran yang lebih efektif dalam merespons kebutuhan spiritual dan moral peserta didik, sambil mempertimbangkan dinamika internalisasi Islam dalam dua dimensi pendidikan.